Decline in Decreased Cephalosporin Susceptibility and Increase in Azithromycin Resistance in Neisseria gonorrhoeae, Canada - Martin, I. (Emerg Infect Dis, 2016)
Antimicrobial resistance profiles were determined for Neisseria gonorrhoeae strains isolated in Canada during 2010–2014. The proportion of isolates with decreased susceptibility to cephalosporins declined significantly between 2011 and 2014, whereas azithromycin resistance increased significantly during that period. Continued surveillance of antimicrobial drug susceptibilities is imperative to inform treatment guidelines.